Apakah Perilaku Disfungsional Audit Penting dalam Kaitannya dengan Kualitas Audit Internal? - Muhammad Irsan Nasution; Yulisfan (ARBITRASE: Journal of Economics and Accounting, 2024)
The purpose of this study is to investigate, evaluate, and gather empirical data regarding the potential effects on internal audit quality of premature sign-off, underreporting time dan reducing audit procedure. Internal auditors in North Sumatra's provinces, districts, and cities make up the research's population. Primary data obtained via questionnaires is what was used. A Google Form was used to collect the data. The Smart PLS application is used for hypothesis testing. This study's data analysis approach makes use of multiple linear regression analysis. The findings of this study offer significant insights for inspectorates, as well as province, district, and local governments in North Sumatra regarding the elements that contribute to dysfunctional audit behavior. Today's auditors must devise standards and broaden their audit procedures in order to sufficiently oversee entity activities. According to the study's findings, there was a negatively considerable impact on internal audit quality from premature sign-off, underreporting time dan reducing audit procedure. The research's findings support the theory that was put forth and are consistent with it.